Some Existence Results of Positive Solutions for φ-Laplacian Systems - Xianghui Xu; Yong-Hoon Lee (Abstract and Applied Analysis)
We study the existence of positive solutions for the homogeneous Dirichlet boundary value problem of φ-Laplacian systems with a singular weight which may not be in L1.